Generation of the induced pluripotent stem cell line CSSi006-A (3681) from a patient affected by advanced-stage Juvenile Onset Huntington's Disease - Giovannina Rotundo; Eris Bidollari; Daniela Ferrari; Iolanda Spasari; Laura Bernardini; Federica Consoli; Alessandro De Luca; Iolanda Santimone; Giuseppe Lamorte; Simone Migliore; Ferdinando Squitieri; Angelo Luigi Vescovi; et al. (Stem Cell Research, 2018)
Juvenile Onset Huntington's Disease (JOHD) is a rare variant of HD withage of onset ≤20 years, accounting for 3–10% of all HD patients. The rarity occurrence of JOHD cases, who severely progress towards mental and physical disability with atypical clinical manifestations compared to classical HD, are responsible of general lack of knowledge about this variant. We obtained a fully reprogrammed iPS cell line from fibroblasts of a JOHD patient carrying 65 CAG repeats and age at onset at age 15. At the biopsy time, the patient showed an advanced stage after 10 years of disease.